Ketahanan Pangan Sebagai Konsep Masterplan Destinasi Wisata Sendang Sombomerti, Maguwoharjo, Depok, Sleman - Anna Pudianti; Vincentia Reni Vitasurya; Rurdwiarti Lucia Asdra; Vasthi Gianni Agmi Putri; Kelly Lim; Aurelia Tita Kusumajati; Andreas Banyuaji Nugroho; Kelvin (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
Abstract — Sendang Sombomerti is a tourist attraction that was developed side by side with fisheries cultivation. The concept of food security is an exploration of a concept aimed at strengthening fish production by strengthening the potential for bathing tourism originating from the Sombomerti Spring. The integration of these two production and recreation activities aims to prepare the Sendang Sombomerti, Maguwoharjo, Depok, Sleman Tourism Destination Masterplan. Lumbung Padi Mataram was appointed as a regional planning concept that was intended to emphasize its main function of fish cultivation, but it was equipped with tourist facilities. The function and form of the design use a basic grid shape combined with a curved shape, which reflects the combination of a formal cultivation function with a curved shape, symbolizing the recreational function. Tourism with a water theme was developed to connect with fish farming.